2021
DOI: 10.1038/s41370-021-00361-1
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits associated with satellite observed flooding during and following Hurricane Harvey

Abstract: BACKGROUND: Flooding following heavy rains precipitated by hurricanes has been shown to impact the health of people. Earth observations can be used to identify inundation extents for subsequent analysis of health risks associated with flooding at a fine spatio-temporal scale. OBJECTIVE: To evaluate emergency department (ED) visits before, during, and following flooding caused by Hurricane Harvey in 2017 in Texas. METHODS: A controlled before and after design was employed using 2016-2018 ED visits from flooded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 60 publications
0
22
0
1
Order By: Relevance
“…The next month, Hurricane Ida rapidly intensified over a 24-hour period from a Category 1 to a Category 4 storm as it struck New Orleans, creating power outages affecting 1 million homes, putting tens of thousands under evacuation orders, and leading to a curfew to protect people from theft 65 . The hurricane then tracked northward, flooding populous urban areas in the Northeast United States, including New York City, where tens of thousands were displaced or had no running water, and half a million were under boilwater orders 66 .…”
Section: Extreme Cold: "Everything Gets Worse If You Don't Have Elect...mentioning
confidence: 99%
“…The next month, Hurricane Ida rapidly intensified over a 24-hour period from a Category 1 to a Category 4 storm as it struck New Orleans, creating power outages affecting 1 million homes, putting tens of thousands under evacuation orders, and leading to a curfew to protect people from theft 65 . The hurricane then tracked northward, flooding populous urban areas in the Northeast United States, including New York City, where tens of thousands were displaced or had no running water, and half a million were under boilwater orders 66 .…”
Section: Extreme Cold: "Everything Gets Worse If You Don't Have Elect...mentioning
confidence: 99%
“…Remote sensing products are helpful in demarcating flooded areas to analyze the change in flood related health outcomes during and following flooding (Ramesh et al., 2022; D. Saulnier et al., 2018). Classifying the flooding status of Census tracts following Hurricane Harvey using remotely sensed data, it was found that emergency department visits related to insect bites, acute respiratory infections, pregnancy complications, and intestinal infectious diseases were increased for residents from flooded Census tracts compared to residents of non‐flooded Census tracts (Ramesh et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite images have been widely used to evaluate disaster situation across the world. Balaji Ramesh et al have used satellite images to detect flooding areas post hurricanes [2], while Michele Gazzea et al has developed some deep learning models for the assessment of the damage of railways [3]. Effective methods of evaluating and assessing the damage of damaged facilities, including buildings, are of high value when handling with the aftermath: both saving people in time, and diminishing the economic loss as much as possible.…”
Section: Introductionmentioning
confidence: 99%